Narrative and the Politics of Identity: Patterns of the Spread and Acceptance of Radicalism and Terrorism in Indonesia - Syam, Firdaus (Religions, 2020)
This study aims to examine Islamic narratives heard at mosques and in study groups in the greater metropolitan area of Jakarta, Indonesia. The article asks if youth and leaders of youth organizations in Jakarta are receptive to radical/terrorist discourse or if they deliberate and weigh what certain narratives mean. Qualitative in-depth interviews were conducted with 24 subjects. These included Rohani Islamic group leaders who hold extracurricular study groups after middle and high school classes, as well as Islamic Mission organizations or Lembaga Da’wah Kampus (LDK—literally translates as Campus Mission Organization; they are some senior students and may invite Islamic scholars or themselves teach Islam and preach to students who are willing to learn Islam specially only at the university as an extracurricular activity; in this article, we translate it as Islamic Mission organization.). which exist on Jakarta’s university campuses where radical narratives are discussed. Other organizations and their leaders were also included. Questions posed to members of these organizations by the authors of this article asked if they accepted, rejected, or negotiated certain ideas regarded as radical by the Indonesian government. Respondents were asked if they believed violent acts against non-reform Muslims and non-Muslims were justified. Respondents were also asked if the Indonesian constitution, Pancasila, should continue its secular democratic legal format, or if it should be replaced by sharia law. Ultimately, most informants took more moderate stances, somewhere in between pure secularism and pure radical terrorism. In this way, this study disproves scholars such as Martin van Bruinessen (2013) who claim that Indonesian Islam is becoming more conservative, and others such as Harsono who claim Indonesian Islam is becoming more violent. While violence was condoned by some respondents, this article reveals that a majority of respondents rejected the view that sharia law should prevail. Ultimately most respondents in this study decided a balanced viewpoint was the best. Thus, this article reveals the degree of moderation of most Jakarta residents, and the nuance and depth of consideration that devout individuals give to a range of contemporary ideas as they negotiate their stance on religion, the state, and their local identities.